Platonism and Naturalism : The Possibility of Philosophy - Gerson, Lloyd P. (Book collections on Project MUSE., 2020)
"An account of the central tradition in the history of philosophy, Platonism, along with the class of philosophical positions collectively known as Naturalism and the 'anti-Platonism' of Naturalism both in antiquity and in contemporary philosophy"--